2020
DOI: 10.1016/j.jcp.2020.109736
|View full text |Cite
|
Sign up to set email alerts
|

Non-linearly stable reduced-order models for incompressible flow with energy-conserving finite volume methods

Abstract: A novel reduced-order model (ROM) formulation for incompressible flows is presented with the key property that it exhibits non-linearly stability, independent of the mesh (of the full order model), the time step, the viscosity, and the number of modes. The two essential elements to non-linear stability are: (1) first discretise the full order model, and then project the discretised equations, and (2) use spatial and temporal discretisation schemes for the full order model that are globally energy-conserving (i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…projecting the fully discrete system, simplifies the treatment of the velocity boundary conditions. A recent study on ROMs on a staggered grid [44] demonstrated that the boundary conditions of the discrete FOM can be inherited by the ROM via the projection of the boundary vectors. With this approach, no additional boundary control method, such as the commonly applied penalty function [51,21,52,53] or lifting function methods [51,54,55,56], is needed to handle the BCs at the ROM level.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…projecting the fully discrete system, simplifies the treatment of the velocity boundary conditions. A recent study on ROMs on a staggered grid [44] demonstrated that the boundary conditions of the discrete FOM can be inherited by the ROM via the projection of the boundary vectors. With this approach, no additional boundary control method, such as the commonly applied penalty function [51,21,52,53] or lifting function methods [51,54,55,56], is needed to handle the BCs at the ROM level.…”
Section: Introductionmentioning
confidence: 99%
“…We employ explicit time integration methods instead of implicit ones at the FOM and the ROM level in order to ease the derivations [57]. We base our approach on the recent progression on ROMs on staggered grids [44]. First of all, we project the fully discrete system, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations